FORECASTING MONTHLY INFLATION IN POLAND BY INDEX METHOD AND FOURIER ANALYSIS - Kisielińska, Joanna (Acta Scientiarum Polonorum. Oeconomia, 2003)
The paper presents models of inflation constructed with index method and Fourier analysis. Both methods make possible to present its periodic character. For each method two types models were made – additive and multiplicative. The comparison based on root average square error ex post for years 1991–2002, and root average square error for January and February 2003. The calculations show distinct prevalence of multiplicative models to additive. In the article there were presented various inflation definitions.